They’re Called “Specialty Courts” for a Reason: A Criminologically-informed and Evidence-based Reply to Lucas (2020) - Pratt, Travis C. (Victims & offenders, 2021)
We recently published an article in Victims & Offenders in which we argued that: (1) the generality of deviance is real (i.e., offenders rarely specialize in any form of criminal or deviant behavior), (2) specialty courts typically assume - either implicitly or explicitly - that offenders do, in fact, specialize primarily in a particular form of criminal behavior, and (3) that there is thus a mismatch between a well-documented criminological reality and the administrative reality of specialty courts. Lucas recently took issue with our arguments and claimed that specialty courts are well-run, evidence based, and sufficiently flexible to be consistently effective at reducing recidivism, and that our relative pessimism is rooted in our “misinterpretation” of the evidence we cite. We find no merit in either of his arguments and we present here a criminologically-informed and evidence-based discussion of the generality of deviance and specialty courts.